EXPLORING THE USE OF EDMODO IN AN EFL CLASSROOM - Gabrina, Putri Alfa Sobri; Rahmawati, Fitria (Journal of Foreign Language Teaching and Learning, 2019)
The use of a Learning Management System (LMS) in education, including in English as Foreign Language classrooms, is widely deliberated ever since the appearance of Web 2.0 technology. Its use as a virtual classroom works as an alternative approach of teaching that allows teachers and students to perform various tasks and functions. For students, it eases them to both learn and practice the target language. This paper aims to report insights on how EFL students perceived the use of LMS, especially Edmodo. The researchers gathered data by interviewing four EFL students of a private Islamic university in Yogyakarta. The results clarify their impression towards Edmodo depicted in two main aspects; the features and activities when utilizing Edmodo. The participants reported a positive belief in the integration of Edmodo in language learning. The research also found that students' backpacks, quizzes, assignments, posts, and comments were useful features that assist them. Besides, the participants explained how they integrated Edmodo in the EFL classroom, including undertaking quizzes, submitting the assignment, practicing writing, speaking, reading, and listening. This study suggested that Edmodo is a valuable tool for learning languages.